2000
DOI: 10.1080/00222890009601385
|View full text |Cite
|
Sign up to set email alerts
|

Monocular and Binocular Vision in the Control of Goal-Directed Movement

Abstract: In the present research the authors examined the time course of binocular integration in goal-directed aiming and grasping. With liquid-crystal goggles, the authors manipulated vision independently to the right and left eyes of 10 students during movement preparation and movement execution. Contrary to earlier findings reported in catching experiments (I. Olivier, D. J. Weeks, K. L. Ricker, J. Lyons, & D. Elliott, 1998), neither a temporal nor a spatial binocular advantage was obtained in 1 grasping and 2 aimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…combine to provide sufficient information to perform goal-directed aiming similar to that exhibited in normal conditions of binocular vision (Jackson et al, 1997;Watt and Bradshaw, 2000). In a series of studies by our group, we have shown that this is particularly true if the object-of-interest is located at a predictable location and the movement is performed under full vision conditions (Coull et al, 2000). The availability of information throughout the movement, combined with tactile feedback upon movement completion, enables the participant to develop an effective internal model and online control over repeated trials.…”
Section: Controlmentioning
confidence: 79%
“…combine to provide sufficient information to perform goal-directed aiming similar to that exhibited in normal conditions of binocular vision (Jackson et al, 1997;Watt and Bradshaw, 2000). In a series of studies by our group, we have shown that this is particularly true if the object-of-interest is located at a predictable location and the movement is performed under full vision conditions (Coull et al, 2000). The availability of information throughout the movement, combined with tactile feedback upon movement completion, enables the participant to develop an effective internal model and online control over repeated trials.…”
Section: Controlmentioning
confidence: 79%
“…The significant difference between the 2‐D and 3‐D displays may also be associated with the task used in the present study. A review of the cognitive literature revealed that verbal judgement tasks (e.g., distance estimation and elevation estimation) were not sensible to the 2‐D and 3‐D displays, while the differences between 2‐D and 3‐D displays were usually observed in tasks that required motor action (Coull, Weir, Tremblay, Weeks, & Elliott, ; Marotta & Goodale, ; Marotta, Perrot, Nicolle, Servos, & Goodale, 1995). In our study, the participants were required to handle the control marker to catch the target; thus, the tracking performance with the 3‐D display (relative to 2‐D the display) significantly decreased, as shown by the longer tracking times and increased tracking errors.…”
Section: Discussionmentioning
confidence: 99%
“…Marotta and Goodale () found that, when binocular information is unavailable, subjects could use the learned relationship between an object's elevation and its distance as a cue to guide their grasping movements. Recent research has also shown that individuals are able to perform equally well under monocular vision (Coull et al, ; Servos & Goodale, ). In fact, experts could develop cognitive mechanisms to compensate for the loss of depth perception in the 2‐D view.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies show that adult reaching is largely uninfluenced by monocular viewing conditions (Coull et al 2000; Heat et al 2008). Monocular viewing leads to increased spatial variance, which in turn gives rise to longer movement durations (Loftus et al 2004; Marotta et al 1995).…”
Section: Introductionmentioning
confidence: 99%